Enhancement of CO2/N2 selectivity and CO2 uptake by tuning concentration and chemical structure of imidazolium-based ILs immobilized in mesoporous silica. Issue 3 (June 2020) - Duczinski, Rafael; Polesso, Barbara B.; Bernard, Franciele L.; Ferrari, Henrique Z.; Almeida, Pedro L.; Corvo, Marta C.; Cabrita, Eurico J.; Menezes, Sonia; Einloft, Sandra
Graphical abstract: Abstract: Imidazolium-based ionic liquids (ILs) with different cation alkyl chain ([ i -C5 mim] or [C4 mim]) and inorganic anions ([Cl − ], [Tf2 N − ], [PF6 − ] and [DCA − ]) were synthesized and immobilized in commercial mesoporous silica. The synthesized supported ILs (SILs) were characterized using NMR, FTIR, TGA, BET, SEM and TEM. CO2 sorption capacity, reusability and CO2 /N2 selectivity were assessed by the pressure-decay technique. The effects of IL concentration, cation and anion chemical structure in CO2 sorption capacity and CO2 /N2 separation performance were evaluated. Tests evidenced that the presence of branching on the cation alkyl side chain increases CO2 /N2 selectivity. The immobilization of the IL [ i -C5 TPIm][Cl] on mesoporous silica in different concentrations (50, 20, 10 and 5 %) revealed that lower IL concentration results in higher CO2 sorption capacity. Immobilization of ILs containing fluorinated anions at low concentrations in the mesoporous silica support may promote the improvement of the CO2 /N2 selectivity without interfering on CO2 sorption capacity of the original support. CO2 sorption capacity value shown by sample SIL-5 % - [ i -C5 TPIm][Tf2 N] (79.50 ± 0.70 mg CO2  g -1 ) was close to the value obtained for the pristine mesoporous silica (81.70 ± 2.20 mg CO2  g -1 ) and the selectivity (4.30 ± 0.70) was more than twice of the one obtained for the support alone (2.32 ± 0.4). Recycle tests demonstrated that the ILs immobilized in mesoporous silica samples are stable, providing a new option to be used in CO2 capture processes.